Repeat vaccination reduces antibody affinity maturation across different influenza vaccine platforms in humans - Surender Khurana (Nature Portfolio, 2019)
Here, Khurana et al. report the results of a phase 4 clinical trial with three FDA approved influenza vaccines and show that repeat influenza vaccination results in reduced antibody affinity maturation to hemagglutinin domain 1 irrespective of vaccine platform.